Changing Demographic Trends in spine trauma: The presentation and outcome of Major Spine Trauma in the elderly. Issue 6 (December 2022) - Nagassima Rodrigues Dos Reis, Katharina; McDonnell, Jake M.; Ahern, Daniel P.; Evans, Shane; Gibbons, Denys; Butler, Joseph S.
Abstract: Introduction: Major trauma has seen a demographic shift in recent years and it is expected that the elderly population will comprise a greater burden on the major trauma service in the near future. However, whether a similar trend exists in those undergoing operative intervention for spinal trauma remains to be elucidated. Aims: To compare the presentation and outcomes of patients ≥65 years of age sustaining spine trauma to those <65 years at a national tertiary referral spine centre. Methods: The local Trauma Audit Research Network (TARN) database was analysed to identify spinal patients referred to our institution, a national tertiary referral centre, between 01/2016 and 05/2019. Patients were divided into a young cohort (16–64 years old) and an elderly cohort (> 64 years old). No explicit distinction was made between major and minor spine trauma cases. Variables analysed included patient demographics, injury severity, mortality, interventions, mechanism of injury and length of hospital stay. Results: A total of 669 patients were admitted of which 480 patients underwent operative intervention for spinal trauma. Within the elderly cohort, this represented 75.3% of cases. Among the younger population, road traffic collisions were the most common mechanism of injury (37.1%), while low falls (<2 m) (57.4%) were the most common mechanism among the older population. Patients ≥65 years old had significantly longer length of stay (21 days [1–194] v 14 days [1–183]) and suffered higher 30-day mortality rates (4.6% [0–12] v 0.97% [0–4]). Conclusion: Orthopaedic spinal trauma in older people is associated with a significantly higher mortality rate as well as a longer duration of hospitalization. Even though severity of injury is similar for both young and old patients, the mechanism of injury for the older population is of typically much lower energy compared to the high energy trauma affecting younger patients. Highlights: Low falls were the most common mechanism of injury among the older population Fixation ± fusion was the most common surgical intervention in elderly patients Elderly patients had a significantly longer length of stay and suffered higher 30-day mortality rates.